3(x-5)=2(x+1)+x

Simple and best practice solution for 3(x-5)=2(x+1)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)=2(x+1)+x equation:


Simplifying
3(x + -5) = 2(x + 1) + x

Reorder the terms:
3(-5 + x) = 2(x + 1) + x
(-5 * 3 + x * 3) = 2(x + 1) + x
(-15 + 3x) = 2(x + 1) + x

Reorder the terms:
-15 + 3x = 2(1 + x) + x
-15 + 3x = (1 * 2 + x * 2) + x
-15 + 3x = (2 + 2x) + x

Combine like terms: 2x + x = 3x
-15 + 3x = 2 + 3x

Add '-3x' to each side of the equation.
-15 + 3x + -3x = 2 + 3x + -3x

Combine like terms: 3x + -3x = 0
-15 + 0 = 2 + 3x + -3x
-15 = 2 + 3x + -3x

Combine like terms: 3x + -3x = 0
-15 = 2 + 0
-15 = 2

Solving
-15 = 2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 | | (10+2x)(20+2x)=336 | | 7x+6=3x+2 | | 2x-16y=7 | | 6(6g-2)+8(1+5g)=2g | | 6n-32=3n+7 | | 2x^2-4x=1.33333 | | 7t-6=330 | | (7+u)(5u-6)=0 | | 7x+8x+2x=12 | | -69=6(-3n-2)-(-5n-8) | | 19=x-32 | | A(-8)= | | 2y=x+13 | | 1+2p=16+7p | | 8x+15=5x+6 | | 9-x-4=45 | | A(2)= | | -5*-3=13-3m | | A(2)=8 |

Equations solver categories